Characteristics of eye disorders induced by atypical antipsychotics: a real-world study from 2016 to 2022 based on Food and Drug Administration Adverse Event Reporting System - Mu, Chao; Chen, Li (Frontiers in Psychiatry, 2024)
ABSTRACT Background：Common atypical antipsychotics include risperidone, paliperidone, olanzapine, lurasidone, quetiapine, clozapine, aripiprazole, ziprasidone, asenapine, brexpiprazole, and cariprazine. Previous studies on ocular adverse reactions of antipsychotics were mainly focused on typical antipsychotics. Systematic research on atypical antipsychotics remains limited. Objective: This study aimed to evaluate the potential risks of different atypical antipsychotics causing ocular side effects by mining the Food and Drug Administration Adverse Event Reporting System (FAERS) database. Methods: Extract reports from the FAERS from the first quarter of 2016 to the fourth quarter of 2022 were obtained. Data mining of eye disorders associated with atypical antipsychotics was carried out using The Reporting Odds Ratio (ROR) method and The Medicines and Healthcare Products Regulatory Agency (MHRA) method to determine positive signals. Results: FAERS reports for 9913783 cases were included in these 28 quarters. 64 defined ocular adverse events were classified into 10 categories according to High-Level Group Terms (HLGT). Conclusions: There were differences in the types and severity of ocular-related adverse events associated with atypical antipsychotics. Ocular neuromuscular-related adverse events were found among all 11 atypical antipsychotics. Olanzapine had the highest signal intensity in oculogyric crisis. Aripiprazole had the highest signal strength in blepharospasm. Cariprazine was associated with cataract-related ocular adverse reactions. In terms of the types of adverse events, our study found that aripiprazole was associated with 28 types of ocular adverse events, followed by quetiapine. Clozapine was only associated with two types of ocular adverse events.